STUDY OF THE EFFECTIVENESS OF MEDICINE NO. 5 ON A MODEL OF DRY EYE SYNDROME IN RABBITS - Pletnev Vladimir Vladimirovich (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
On the model of dry eye syndrome in rabbits, it is shown that the medicine No. 5 at a dose of 0.05 ml/kg in 1:15 dilution with sterile saline solution when instilled into both eyes of animals 2 times a day for 30 days has a strong anti-inflammatory, wound-healing and angioprotective effects, positively affecting the course of the reparative process in the conjunctiva, cornea, complicated by the condition of non-closing of the eyelids. It was also found that the medicine No. 5 in the tested dose promotes the stimulation of reparative processes in the conjunctiva, cornea, clinically manifesting itself in accelerating the recovery of defects in the anterior epithelium and corneal stroma, in reducing the frequency of formation of deep corneal defects, reducing the severity of inflammatory response and vascularization. There is a slowdown in the formation of corneal opacities, a decrease in the amount and appearance of a more liquid mucous discharge of the conjunctiva compared to the control. On the model of dry eye syndrome in rabbits, it was shown that drug No. 5 in the test dose has a pronounced pharmacological effect, contributing to a faster recovery of damage to the superficial epithelium and stroma of the cornea, anterior and posterior chambers of the eye, the vascular membrane and retina, as well as goblet cells of the conjunctiva.